Ecological Viability of Bamboo as an Alternative Revegetation Species for Post-Andesite Mining Land: A Comparative Assessment with Pioneer Species - Tjahjo Tri Hartono; Aidha Zulaika; Harsono (Universitas Ibn Khaldun Bogor, 2025)
Andesite mining activities cause land degradation that requires revegetation efforts for ecosystem restoration. This study aims to evaluate the ecological feasibility of bamboo as an alternative revegetation species for post-mining sites compared to conventional pioneer plants through a systematic literature review. Analysis was conducted on 45 relevant scientific publications from indexed academic databases, focusing on adaptability, soil improvement, erosion control, and contribution to biodiversity. Results show that bamboo has significant advantages in root systems (fine root biomass 1.1-4.5 kg m⁻³), erosion control effectiveness, and carbon sequestration potential (6-13 Mg ha⁻¹ year⁻¹). Bamboo also demonstrates high adaptability to marginal land conditions and provides sustainable economic value through selective harvesting without damaging the root system. Compared to conventional pioneer plants, bamboo provides more stable long-term contributions to post-mining ecosystem restoration. This study recommends the use of bamboo as a primary component in andesite post-mining land revegetation programs in Indonesia.